PERBEDAAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DAN TIPE TEAMS GAMES TOURAMENT (TGT) BERBANTUAN MEDIA WORD SQUARE - abqoriyah, Zahra; Nurdianti, Raden Roro Suci; Srigustini, Astri (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The main problem related to this research is the low learning outcomes of students in economics subjects. This research aims to determine whether there is a significant difference in the learning outcomes of students who use the cooperative model of the Student Teams Achievement Division (STAD) type and the Teams Games Tournament (TGT) type assisted by Word Square media before and after treatment. This research was carried out at SMA Negeri 1 Cihaurbeuti. The research method used was a quasi-experimental method. The research design used was matching pretest – posttest control group design. The population in this study were all students in class The research sample was taken using a purposive sampling technique, namely experimental class 1 (STAD) with 36 students and experimental class 2 (TGT) with 36 students. The instrument used is multiple choice questions in economics subjects which have previously been tested. The test results of 35 questions were valid and the test reliability was 0.927. The data analysis technique uses the help of the SPSS 29 program. Based on the results of the research that has been carried out, the average learning outcomes of students in experimental class 1 (STAD) and experimental class 2 (TGT) are 78.78 and 84.42 with an increase in learning outcomes. STAD is 65% and in the TGT class it is 74%. Based on the results of data analysis, it was found that the data was normally distributed and both samples came from a homogeneous population. Based on the results of data analysis, namely the paired sample t test and the independent sample t test with a significance level of 5% or 0.05, a significance value of 0.001 was obtained so that it can be concluded that there is a difference in the increase in student learning outcomes in experimental class 1 which uses the cooperative learning model. Student Teams Achievement Division (STAD) type assisted by Word Square media after being given treatment and in experimental class 2 which used the Teams Games Tournament (TGT) type cooperative learning model assisted by Word Square media after being given treatment